Tab glue, negative plate and lithium ion battery
By controlling surface tension and viscosity in the ear glue of lithium-ion batteries and using specific polymer segments, the problem of battery capacity is solved and higher cycling performance is achieved.
Patent Information
- Application Number
- CN202510031779.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2045-01-09
AI Technical Summary
Existing emulsion-like aqueous ear glue will cause a decrease in battery capacity during the processing of lithium-ion batteries.
An extreme ear glue is provided, the surface tension of the emulsion is 45-60 mN/m, the viscosity is 2000 mPa·s or more, and includes a specific polymer segment to suppress the occurrence of string materials and the loss of electrode capacity.
By controlling the surface tension and viscosity of the elbow glue, the occurrence of string materials is suppressed, the battery capacity loss is reduced, and the circulation performance of lithium-ion batteries is improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a tab glue, in particular to a tab glue, a negative electrode sheet and a lithium ion battery. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic devices, electric bicycles, electric vehicles, aerospace and other fields due to their high energy density, long cycle life, low self-discharge rate, wide operating temperature range, and green environmental protection.
[0003] During the processing of lithium-ion batteries, the negative electrode sheets often need to be die-cut for welding the tabs; however, during the die-cutting process, the edge of the negative electrode current collector copper foil may have burrs due to cutting, and such metal burrs may cause short circuits during battery operation, leading to battery abnormalities. At present, it is common to effectively avoid the appearance of burrs and improve battery safety by coating an insulating layer (usually including ceramic particles and tab glue) on the edge area of the copper foil; moreover, in some special batteries, such as blade batteries, in order to prevent the misalignment between the electrode sheet and the diaphragm when entering the shell, the tab glue in the ceramic layer is also required to bond the diaphragm to the electrode sheet.
[0004] At present, the ear glue for negative electrode is generally a water-based emulsion binder. This emulsion binder uses water as the dispersion medium and has the characteristics of high environmental protection, safety and adhesion; however, it often leads to a decrease in battery capacity. Summary of the invention
[0005] Aiming at the defect that the existing emulsion-like water-based ear glue may cause the battery capacity to decrease, the present invention provides an ear glue, which is beneficial to suppress the battery capacity loss.
[0006] The present invention also provides a negative electrode sheet, comprising the above-mentioned ear glue, so the negative electrode sheet is applied to a lithium ion battery to effectively reduce capacity loss.
[0007] The present invention also provides a lithium ion battery, which includes the above-mentioned ear glue or the above-mentioned negative electrode sheet, so the battery has higher cycle performance.
[0008] A first aspect of the present invention provides a tab glue, wherein the tab glue is an emulsion, wherein the surface tension of the emulsion is 45-60 mN / m, and the viscosity is above 2000 mPa·s.
[0009] Usually when preparing the electrode sheet, it is necessary to first coat the electrode slurry on the surface of the current collector, and reserve some blank current collectors at the edge of the electrode slurry coating area to form the pole ear, and then coat the insulating slurry containing the pole ear glue on the blank area to form an insulating layer, and the insulating layer will overlap with the coating area of the electrode slurry. However, the applicant has found that an emulsifier is usually required to stabilize the latex micelle particles in the existing emulsion-like pole ear glue, and the emulsifier is usually difficult to remove and will cause cross-linking between the insulating slurry and the electrode slurry, thereby causing a loss of electrode capacity. The present invention can effectively suppress the occurrence of cross-linking by controlling the surface tension and viscosity of the pole ear glue latex within the above range, thereby suppressing the loss of electrode capacity.
[0010] The ear glue as described above, wherein the solid content of the ear glue is 20-25%.
[0011] The tab glue as described above, wherein the tab glue comprises a polymer, the polymer comprises a first polymer segment and a second polymer segment, the glass transition temperature Tg of the first polymer segment is ≥50°C, and the glass transition temperature Tg of the second polymer segment is ≤-30°C.
[0012] When the ear glue contains the above-mentioned polymer segments with different glass transition temperatures, it is very beneficial to improve the bonding strength.
[0013] The ear glue as described above, wherein the first polymer segment includes a first main structural unit, the first main structural unit is an acrylic structural unit, and the second polymer segment includes a second main structural unit, the second main structural unit is an acrylic structural unit;
[0014] The first polymer segment further comprises a strong polar structural unit, wherein the strong polar structural unit comprises at least one of a structural unit containing a carboxyl group, a hydroxyl group, a cyano group, and an amide group;
[0015] The second polymer segment further comprises a weak polar structural unit, and the weak polar structural unit comprises at least one of a structural unit containing an aromatic group and an ester group.
[0016] In the present invention, when the glass transition temperatures of the first polymer segment and the second polymer segment are respectively within the above ranges, and the first polymer segment and the second polymer segment each contain the aforementioned group, when the ear glue is used for the negative electrode plate, the polymer in the ear glue can not only form a strong bonding force with the negative electrode current collector and the separator to achieve a higher peel strength, but also has good wettability with the electrolyte, which helps to reduce the internal resistance of the battery cell and improve its high temperature storage performance and cycle performance.
[0017] The ear glue as described above, wherein in the polymer, the mass ratio of the first polymer segment to the second polymer segment is (5-30):(70-95).
[0018] In the ear glue as described above, the first polymer segment includes a first reactive structural unit, the second polymer segment includes a second reactive structural unit, and the first reactive structural unit and the second reactive structural unit can undergo polymerization reaction under heating conditions.
[0019] The ear glue as described above, wherein the first reactive structural unit and the second reactive structural unit are each independently selected from one or more of a hydroxyl group, an isocyanate group, an epoxy group, and a carboxyl group.
[0020] The ear glue as described above, wherein the mass content of the first reactive structural unit in the first polymer segment is 3-10%;
[0021] And / or, the mass content of the second reactive structural unit in the second polymer segment is 3-10%.
[0022] The second aspect of the present invention provides a negative electrode sheet, comprising a negative electrode collector and a negative electrode material layer arranged on at least a portion of the surface of the negative electrode collector; an insulating layer is also arranged on the surface of the negative electrode collector, and the insulating layer is prepared by an insulating layer slurry including the ear glue of the first aspect.
[0023] A third aspect of the present invention provides a lithium ion battery, comprising the negative electrode sheet of the second aspect. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The first aspect of the present invention provides a tab glue, which is an emulsion, and the surface tension of the emulsion is 45-60 mN / m and the viscosity is above 2000 mPa·s.
[0026] The present invention can effectively inhibit the occurrence of material cross-talk by controlling the surface tension and viscosity of the tab rubber latex within the above range, thereby inhibiting the loss of electrode capacity.
[0027] Preferably, the surface tension of the emulsion is 45 to 60 mN / m, more preferably 50 to 55 mN / m. Specifically, it can be 45 mN / m, 46 mN / m, 47 mN / m, 48 mN / m, 49 mN / m, 50 mN / m, 51 mN / m, 52 mN / m, 53 mN / m, 54 mN / m, 55 mN / m, 56 mN / m, 57 mN / m, 58 mN / m, 59 mN / m or 60 mN / m.
[0028] In the present invention, the "surface tension" of the tab rubber latex can be obtained by testing with a surface tension meter, and the "viscosity" of the tab rubber latex can be obtained by testing with a viscometer.
[0029] In the present invention, the viscosity of the ear glue is 2000mPa·s or more, more preferably 2000-8000mPa·s. Specifically, the viscosity of the ear glue can be 2000mPa·s, 2500mPa·s, 3000mPa·s, 3500mPa·s, 4000mPa·s, 4500mPa·s, 5000mPa·s, 5500mPa·s, 6000mPa·s, 6500mPa·s, 7000mPa·s, 7500mPa·s or 8000mPa·s.
[0030] In a specific embodiment, the solid content of the tab glue is 20-25%. Preferably, the solid content is 21-23%. Specifically, the solid content of the tab glue can be 20%, 21%, 22%, 23%, 24% or 25%.
[0031] To further improve the bonding strength of the tab glue, preferably, the tab glue includes a polymer, the polymer includes a first polymer segment and a second polymer segment, the glass transition temperature Tg of the first polymer segment is ≥50°C, and the glass transition temperature Tg of the second polymer segment is ≤-30°C.
[0032] When the tab glue contains the above-mentioned polymer segments with different glass transition temperatures, it is very beneficial to improve the bonding strength of the tab glue.
[0033] Specifically, the glass transition temperature Tg of the first polymer segment is 50-110°C; and the glass transition temperature Tg of the second polymer segment is -50--30°C.
[0034] The “glass transition temperature Tg” in the present invention refers to the temperature corresponding to the transition from a glassy state to a highly elastic state, which can be obtained by differential scanning calorimetry (DSC) testing.
[0035] Illustratively, the glass transition temperature Tg of the first polymer segment is 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C or 110°C.
[0036] Illustratively, the glass transition temperature Tg of the second polymer segment is -50°C, -48°C, -46°C, -44°C, -42°C, -40°C, -38°C, -36°C, -34°C, -32°C or -30°C.
[0037] In a specific embodiment, in the polymer, the mass ratio of the first polymer segment to the second polymer segment is (5-30):(70-95), specifically 5:95, 10:90, 15:85, 20:80, 25:75 or 30:70.
[0038] In the present invention, when the first polymer chain segment is too much, it is not conducive to further improving the bonding strength between the polymer in the ear glue and the separator; and when the second polymer chain segment is too much, it is not conducive to further improving the bonding strength between the polymer in the ear glue and the negative electrode current collector, especially it may increase the risk of falling off after immersion in the electrolyte. When the mass ratio of the first polymer chain segment to the second polymer chain segment is within the aforementioned range, the ear glue can form a strong bonding strength with the separator and the negative electrode current collector, and is not easy to fall off after immersion in the electrolyte.
[0039] The specific material types of the first polymer segment and the second polymer segment can be adjusted according to actual needs. In the present invention, preferably, the first polymer segment includes a first main structural unit, which is an acrylic structural unit; the second polymer segment includes a second main structural unit, which is an acrylic structural unit.
[0040] Specifically, the acrylic structural unit is selected from one or more of acrylic structural units, methacrylic structural units, ethylacrylic structural units, propylacrylic structural units, fluoroacrylic structural units, cyanoacrylic structural units, aminoacrylic structural units, and hydroxypropylacrylic structural units.
[0041] The acrylic acid ester structural unit is selected from the group consisting of methyl acrylate structural unit, ethyl acrylate structural unit, n-propyl acrylate structural unit, isopropyl acrylate structural unit, n-butyl acrylate structural unit, isobutyl acrylate structural unit, tert-butyl acrylate structural unit, n-pentyl acrylate structural unit, isopentyl acrylate structural unit, n-hexyl acrylate structural unit, n-octyl acrylate structural unit, isooctyl acrylate structural unit, isobornyl acrylate structural unit, phenoxyethyl acrylate structural unit, dicyclopentenyl acrylate structural unit, cyclohexyl acrylate structural unit, benzyl acrylate structural unit, methyl methacrylate structural unit, ethyl methacrylate structural unit, n-propyl methacrylate structural unit, isopropyl methacrylate structural unit, n-butyl methacrylate structural unit, isobutyl methacrylate structural unit, tert-butyl methacrylate structural unit, n-pentyl methacrylate structural unit, methacrylic acid structural unit, At least one of an isopentyl methacrylate structural unit, a n-hexyl methacrylate structural unit, an isooctyl methacrylate structural unit, an isobornyl methacrylate structural unit, a phenoxyethyl methacrylate structural unit, a dicyclopentenyl methacrylate structural unit, a cyclohexyl methacrylate structural unit, a benzyl methacrylate structural unit, an ethylene glycol diacrylate structural unit, an ethylene glycol dimethacrylate structural unit, an ethoxylated ethylene glycol diacrylate structural unit, an ethoxylated ethylene glycol dimethacrylate structural unit, an allyl methacrylate structural unit, a diallyl phthalate structural unit, an adipate diallyl structural unit, a trimethylolpropane triacrylate structural unit, a trimethylolpropane trimethacrylate structural unit, a pentaerythritol diacrylate structural unit, a pentaerythritol dimethacrylate structural unit, a pentaerythritol triacrylate structural unit, and a pentaerythritol trimethacrylate structural unit.
[0042] Furthermore, the first polymer segment also includes a strong polar structural unit, which includes at least one of the structural units containing carboxyl, hydroxyl, cyano, and amide groups; the second polymer segment also includes a weak polar structural unit, which includes at least one of the structural units containing aromatic groups and ester groups.
[0043] In the present invention, the strong polar structural unit in the first polymer segment can be obtained by adding a monomer containing a corresponding strong polar group (i.e., at least one of a carboxyl group, a hydroxyl group, a cyano group, and an amide group) during the formation of the first polymer segment; the weak polar structural unit in the second polymer segment can be obtained by adding a monomer containing a corresponding weak polar group (i.e., at least one of an aromatic group and an ester group) during the formation of the second polymer segment.
[0044] For example, the carboxyl group, hydroxyl group, cyano group, and amide group in the first polymer segment can be introduced through one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxybutyl methacrylate, acrylonitrile, methacrylonitrile, acrylamide, and hydroxymethyl acrylamide respectively; the aromatic group and ester group in the second polymer segment can be introduced through one or more of styrene, methylstyrene, ethyl acrylate, butyl acrylate, isooctyl acrylate, and lauryl acrylate respectively.
[0045] The content of the strongly polar structural unit in the first polymer segment can vary within a wide range. Preferably, the mass ratio of the first main structural unit to the strongly polar structural unit is (50-95):(2-40).
[0046] The content of the weak polar structural unit in the second polymer segment can vary within a wide range. Preferably, the mass ratio of the second main structural unit to the weak polar structural unit is (50-95):(2-40).
[0047] The content of the strong polar structural unit in the first polymer segment is the ratio of the weight of the strong polar monomer corresponding to the strong polar structural unit to the weight of the monomer corresponding to the first main structural unit in the raw material monomers for preparing the first polymer segment. Similarly, the content of the weak polar structural unit in the second polymer segment is the ratio of the weight of the weak polar monomer corresponding to the weak polar structural unit to the weight of the monomer corresponding to the second main structural unit in the raw material monomers for preparing the second polymer segment.
[0048] It can be understood that when the strong polar structural unit in the first polymer segment is an acrylic structural unit and / or a methacrylic structural unit, at this time, the strong polar group is the same as the first main structural unit, and there is no need to distinguish between the strong polar structural unit and the first main structural unit; and in the first polymer segment, the total content of the acrylic structural unit and / or the methacrylic structural unit is the sum of the contents of the strong polar structural unit and the first main structural unit defined in the present invention.
[0049] Similarly, when the weak polar structural unit in the second polymer segment is an acrylate structural unit and / or a methacrylate structural unit, at this time, the weak polar group is the same as the second main structural unit, and there is no need to distinguish between the weak polar structural unit and the second main structural unit; and in the second polymer segment, the total content of the acrylate structural unit and / or the methacrylate structural unit is the sum of the contents of the weak polar structural unit and the second main structural unit defined in the present invention.
[0050] In the present invention, when the glass transition temperatures of the first polymer segment and the second polymer segment are respectively within the above ranges, and the first polymer segment and the second polymer segment each contain the aforementioned groups, the polymer in the ear glue can not only form a strong bonding force with the negative electrode current collector and the separator to achieve a higher peel strength, but also has good wettability with the electrolyte, which helps to reduce the internal resistance of the battery cell and improve its high temperature storage performance and cycle performance.
[0051] According to the present invention, the first polymer segment further includes a first reactive structural unit, and the second polymer segment further includes a second reactive structural unit. The first reactive structural unit and the second reactive structural unit can undergo polymerization reaction under heating conditions.
[0052] Specifically, the first reactive structural unit and the second reactive structural unit are each independently selected from one or more of a hydroxyl group, an isocyanate group, an epoxy group, and a carboxyl group.
[0053] It can be understood that among the above-mentioned reactive structural units, hydroxyl and hydroxyl, hydroxyl and isocyanate, hydroxyl and epoxy, carboxyl and epoxy are matched with each other to form a mutually reactive combination, that is, when the first reactive structural unit or the second reactive structural unit is a hydroxyl group, the other reactive structural unit is selected from at least one of a hydroxyl group, an isocyanate group, and an epoxy group; when the first reactive structural unit or the second reactive structural unit is a carboxyl group, the other reactive structural unit is selected from an epoxy group, and vice versa.
[0054] As a specific example, the first reactive structural unit and the second reactive structural unit are each independently selected from at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, hydroxypropyl methacrylate, hydroxymethyl acrylamide, blocked isocyanate curing agent, epoxy resin, acrylic acid, methacrylic acid, and β-acryloxypropionic acid.
[0055] In the present invention, the content of the first reactive structural unit and the second reactive structural unit can vary in a wide range. Preferably, the mass content of the first reactive structural unit in the first polymer segment is 3-10%. Similarly, the mass content of the second reactive structural unit in the second polymer segment is 3-10%.
[0056] The present invention does not specifically limit the temperature at which the first reactive structural unit and the second reactive structural unit undergo polymerization reaction, and a suitable reaction temperature can be selected according to actual conditions. For example, the polymerization reaction temperature is 100-110°C.
[0057] In the present invention, the content of the first reactive structural unit and the second reactive structural unit is too high, which is not conducive to the stable storage of the ear rubber latex, and affects the bonding strength between the ear rubber and the negative electrode current collector and the separator to a certain extent. When the mass content of the first reactive structural unit in the first polymer segment is within the aforementioned range, and the mass content of the second reactive structural unit in the second polymer segment is within the aforementioned range, the bonding strength between the ear rubber and the negative electrode current collector and the separator can be further improved.
[0058] Illustratively, the mass content of the first reactive structural unit in the first polymer segment is 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%; the mass content of the second reactive structural unit in the second polymer segment is 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0059] Similar to the aforementioned polar structural unit, the content of the first reactive structural unit is the ratio of the weight of the first reactive monomer corresponding to the first reactive structural unit to the weight of the monomer corresponding to the first polymer segment in the raw material monomers for preparing the first polymer segment. Similarly, the content of the second reactive structural unit is the ratio of the weight of the second reactive monomer corresponding to the second reactive structural unit to the weight of the monomer corresponding to the second polymer segment in the raw material monomers for preparing the second polymer segment.
[0060] When the first polymer segment and the second polymer segment contain the above-mentioned reactive structural unit, the bonding strength of the ear glue to the separator and the negative electrode current collector can be further improved.
[0061] The present invention does not specifically limit the sources of the first polymer segment and the second polymer segment, and the polymers conforming to the present invention can be purchased or prepared by themselves. In one embodiment, they can be obtained by soap-free emulsion polymerization.
[0062] In one embodiment, the method for preparing the first polymer segment comprises the following steps:
[0063] The raw materials including acrylic monomers, monomers containing strong polar groups and first reactive monomers are mixed in a desired proportion to obtain a monomer mixture; the monomer mixture is mixed with water in a volume ratio of 1:(3-5) to obtain a mixed solution; the mixed solution is heated to 70-95° C., an initiator is added, the mass of the initiator is 5-10wt% of the mass of the monomer mixture, the mixture is kept warm for 7-9 hours, stirring is maintained during the reaction, and the stirring speed is 100-450r / min to obtain a first polymer segment.
[0064] The preparation method of the second polymer chain segment can be: mixing an acrylate monomer, a monomer containing a weak polar group, and a second reactive monomer in a desired proportion to obtain a monomer mixture; mixing the monomer mixture with water in a volume ratio of 1:(3~5) to obtain a mixed solution; heating the mixed solution to 70~95°C, adding an initiator, the mass of the initiator being 5~10wt% of the mass of the monomer mixture, and keeping the mixture warm for 7~9h. Stirring is maintained during the reaction at a stirring speed of 100~450r / min to obtain the second polymer chain segment.
[0065] The present invention does not specifically limit the type of initiator, and a conventional water-soluble initiator in the art may be used. For example, at least one of a persulfate initiator and an azo initiator may be selected; wherein the persulfate initiator may be potassium persulfate (K2S2O8) or sodium persulfate (Na2S2O8), and the azo initiator may be 4,4'-azobis(4-cyanovaleric acid).
[0066] The present invention does not specifically limit the heating method during the reaction of the first polymer segment and the second polymer segment, and the heating can be performed in a conventional manner in the art, for example, by heating in a water bath.
[0067] The second aspect of the present invention provides a negative electrode sheet, comprising a negative electrode collector and a negative electrode material layer arranged on at least a portion of the surface of the negative electrode collector; an insulating layer is also arranged on the surface of the negative electrode collector, and the insulating layer is prepared by an insulating layer slurry including the ear glue of the first aspect.
[0068] As is known, the negative electrode current collector is copper foil.
[0069] The present invention does not specifically limit the preparation method of the negative electrode sheet. In one embodiment, the negative electrode sheet can be prepared by the following method:
[0070] The negative electrode active material, binder, conductive agent and solvent are uniformly mixed according to a preset mass ratio to obtain a negative electrode active slurry; the ceramic particles, the first ear glue and the dispersant are uniformly mixed to obtain an insulating layer slurry; the above-mentioned negative electrode active slurry and insulating layer slurry are coated on the negative electrode collector, and the negative electrode sheet is obtained after drying, rolling and slitting.
[0071] The present invention does not specifically limit the types of negative electrode active materials, binders, conductive agents and solvents, and appropriate materials can be selected according to actual conditions.
[0072] For example, the negative electrode active material includes at least one of hard carbon, graphite, and silicon-carbon material.
[0073] The binder includes at least one of styrene-butadiene rubber (SBR), acrylic acid (PAA), and styrene-acrylic emulsion.
[0074] The conductive agent includes at least one of carbon black, graphite, carbon nanotubes, and Ketjen black.
[0075] The solvent is mainly deionized water, with the addition of a small amount of plasticizer such as N-methylpyrrolidone (NMP).
[0076] Generally, the surface tension of the negative electrode active slurry is 55-60 mN / m, and the difference between the surface tension of the tab glue and the surface tension of the negative electrode active slurry is within 10 mN / m.
[0077] In a specific embodiment, the insulating layer includes a bonding substance, ceramic particles and a dispersant; wherein the bonding substance is formed by the polymer in the tab glue of the first aspect; the mass ratio of the ceramic particles, the bonding substance and the dispersant is (60-90): (10-40): 1. Exemplarily, the mass ratio of the ceramic particles, the tab glue (based on the solid content in the tab glue) and the dispersant is 60:40:1, 65:35:1, 70:30:1, 75:25:1, 80:20:1, 85:15:1 or 90:10:1.
[0078] The present invention does not specifically limit the types of ceramic particles and dispersants. For example, the ceramic particles mainly include boehmite and / or alumina, and the dispersant mainly includes polyacrylate and / or sodium carboxymethyl cellulose (CMC).
[0079] The present invention does not specifically limit the sources of the ceramic particles and the dispersant, and commercially available products or products prepared by conventional preparation methods well known to those skilled in the art may be used.
[0080] When the insulating layer includes ceramic particles, ear glue and dispersant in the aforementioned mass ratio, an insulating layer slurry can be prepared which has normal slurry fineness, does not cross-link during coating, does not stick to the roller during rolling, and can achieve bonding between the electrode and the diaphragm during hot pressing.
[0081] The third aspect of the present invention provides a lithium ion battery, which comprises the negative electrode sheet of the second aspect and has lower internal resistance, higher capacity and cycle performance.
[0082] It can be understood that the lithium-ion battery in the present invention also includes a positive electrode sheet, a separator and an electrolyte.
[0083] The present invention does not specifically limit the positive electrode sheet. The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer disposed on at least a portion of the surface of the positive electrode current collector. The positive electrode active layer includes a positive electrode active material, a conductive agent and a binder.
[0084] The positive electrode current collector may be a current collector commonly used in the art, for example, aluminum foil.
[0085] The positive electrode active material includes at least one of lithium cobalt oxide (LCO), lithium nickel cobalt aluminum oxide (NCA), lithium nickel manganese cobalt oxide (NMC), lithium iron phosphate (LFP), and sulfurized polyaramide (SPC).
[0086] The conductive agent includes at least one of graphite, acetylene black, conductive carbon black, conductive carbon fiber, metal oxide, conductive polymer, carbon nanotube, and graphene; wherein the metal oxide includes at least one of titanium dioxide, manganese dioxide, and nickel oxide, and the conductive polymer includes polypyrrole (PPy) and / or polyaniline (PAn).
[0087] The binder includes at least one of polyvinylidene fluoride (PVDF) and polyacrylate.
[0088] The present invention does not impose any specific restrictions on the mass content of the positive electrode active material, the binder and the conductive agent in the positive electrode active layer, and a suitable mass ratio can be selected according to actual needs.
[0089] The present invention does not specifically limit the type of diaphragm, and it can be any diaphragm material commonly used in the art, for example, any one of a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene / polyethylene double-layer composite film (PP / PE), a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), and a diaphragm containing a ceramic coating.
[0090] The present invention does not specifically limit the electrolyte, and may include organic solvents and lithium salts commonly used in lithium-ion battery electrolytes; for example, the organic solvent may include at least one of diethyl carbonate (DEC), ethylene carbonate (EC), ethyl methyl carbonate (EMC), propylene carbonate (PC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl acetate, propyl acetate, ethyl propionate, and propyl propionate; the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), and lithium tetrafluoroborate (LiBF4).
[0091] The ear glue, negative electrode sheet and lithium ion battery provided by the present invention are described in detail below through specific embodiments.
[0092] Example 1
[0093] 1) Preparation of ear glue:
[0094] First polymer segment: 70 parts of acrylic acid, 25 parts of acrylonitrile, 5 parts of hydroxymethyl acrylamide and water were uniformly mixed in a volume ratio of 1:4 to obtain a monomer mixture; the monomer mixture was then heated to 75°C by water bath heating, and then potassium persulfate as an initiator was added, the mass of the initiator was 6wt% of the mass of the monomer mixture, and the reaction was kept warm for 8 hours. Stirring was maintained during the reaction at a stirring speed of 300r / min to obtain a colloidal emulsion of the first polymer segment, and its glass transition temperature was detected to be 105°C;
[0095] Second polymer segment: 90 parts of butyl acrylate, 5 parts of styrene, 5 parts of hydroxymethyl acrylamide, and water were mixed uniformly in a volume ratio of 1:4 to obtain a monomer mixture; the monomer mixture was then heated to 75°C by water bath heating, and then potassium persulfate, an initiator, was added, and the mass of the initiator was 6wt% of the mass of the monomer mixture. The reaction was kept warm for 8 hours, and stirring was maintained during the reaction at a stirring speed of 300r / min to obtain a colloidal emulsion of the second polymer segment, and its glass transition temperature was detected to be -44°C;
[0096] The colloidal emulsion of the first polymer segment and the colloidal emulsion of the second polymer segment were mixed at a polymer mass ratio of 20:80, and the solid content was adjusted to 22%; then, the pH of the mixed system was adjusted to 7 with sodium hydroxide to obtain an ear rubber latex with a surface tension of 51 mN / m, a viscosity of 4253 mPa·s, and a pH of 7.
[0097] 2) Preparation of batteries:
[0098] 96.80 parts of nickel cobalt lithium manganese oxide ternary material, 1.5 parts of conductive agent Super P, 0.5 parts of conductive graphite KS-6, 1.20 parts of binder polyvinylidene fluoride and N-methylpyrrolidone were mixed to prepare a positive electrode slurry, and then the positive electrode slurry was coated on the surface of aluminum foil, and the single-sided surface density after drying and rolling was 180g / m 2 , compacted density is 3.5g / cm 3 The positive electrode.
[0099] Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber (SBR) are mixed in a mass ratio of 93:3:2:2, and deionized water is added and stirred evenly to prepare a negative electrode slurry;
[0100] The aforementioned tab rubber latex (in terms of solid content) is mixed with boehmite and CMC in a mass ratio of 40:60:1 to obtain an insulating layer slurry;
[0101] The negative electrode slurry is coated on the surface of the negative electrode current collector copper foil, and the insulating layer slurry is coated on both sides of the negative electrode slurry layer, and the insulating layer slurry is in contact with the negative electrode slurry but does not overlap; at the same time, an empty foil area is reserved at the edge of the copper foil in the width direction for subsequent cutting of the negative electrode tab; then drying, rolling and slitting are performed to obtain the negative electrode sheet of this embodiment, and the single-sided surface density of the negative electrode sheet is 94g / m 2 , compacted density is 1.6g / cm 3 ;
[0102] The positive electrode sheet, the separator (PP film) and the negative electrode sheet are alternately stacked to form a stacked battery cell;
[0103] The laminated battery cell is placed in an aluminum-plastic film, and the injection port is retained. The electrolyte is injected into the film through the injection port, and then the injection port is closed to obtain a battery precursor; after aging, formation and aging treatment, and after processes such as volume separation, a soft-pack battery is obtained. Among them, the lithium salt in the electrolyte is lithium hexafluorophosphate (LiPF6), the lithium salt concentration is 1M, and the organic solvent is a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a mass ratio of 1:2:1.
[0104] Example 2-Example 8
[0105] The tab glue, negative electrode sheet and battery were prepared according to the method of Example 1, except that the composition of the tab glue was adjusted according to the contents of Table 1 and Table 2. The viscosity, surface tension and solid content of the prepared tab glue are shown in Table 2.
[0106] Comparative Example 1
[0107] The ear glue, negative electrode sheet and battery were prepared according to the method of Example 1, except that in step 1), during the preparation of the first polymer segment, sodium dodecyl sulfate was added at the same time as the initiator, and the mass of the sodium dodecyl sulfate was 1wt% of the mass of the monomer mixture;
[0108] During the preparation of the second polymer segment, sodium dodecyl sulfate is added at the same time as the initiator, and the mass of the sodium dodecyl sulfate is 1 wt % of the mass of the monomer mixture.
[0109] Comparative Example 2
[0110] The ear glue, negative electrode sheet and battery were prepared according to the method of Example 1, except that in step 1), the pH of the mixed system was adjusted to 5 by sodium hydroxide.
[0111] Comparative Example 3
[0112] The ear glue, negative electrode sheet and battery were prepared according to the method of Example 1, except that in step 1), during the preparation of the first polymer segment, sodium dodecyl sulfate was added at the same time as the initiator, and the mass of the sodium dodecyl sulfate was 1wt% of the mass of the monomer mixture;
[0113] During the preparation of the second polymer segment, sodium dodecyl sulfate is added at the same time as the initiator, and the mass of the sodium dodecyl sulfate is 1wt% of the mass of the monomer mixture;
[0114] The pH of the mixed system was adjusted to 5 with sodium hydroxide.
[0115] Table 1
[0116]
[0117] Table 2
[0118]
[0119] Test example
[0120] The lithium ion batteries prepared in the above examples and comparative examples were subjected to the following tests:
[0121] 1) Dry peel strength between the ear glue and the foil
[0122] The negative electrode sheet prepared by the scheme of the present invention was cut into strips of 20*100 mm, pressed for 60 s at 100°C and 8 MPa, and the coating peeling strength was tested using an electronic tensile testing machine (Dongguan Dazhong Instrument Co., Ltd., model DZ-101).
[0123] 2) Wet peel strength between tab glue and foil
[0124] The negative electrode sheet prepared by the scheme of the present invention was cut into strips of 20*100 mm, pressed for 60 s at 100°C and 8 MPa, immersed in an electrolyte at 60°C for 3 days, taken out and dried, and then the coating peeling strength was tested using an electronic tensile testing machine (Dongguan Dazhong Instrument Co., Ltd., Model DZ-101).
[0125] 3) Dry adhesion peel strength between the ear glue and the diaphragm
[0126] The negative electrode sheet and the separator prepared by the scheme of the present invention were cut into strips of 20*100 mm respectively, pressed for 60 s at 100°C and 8 MPa, and the bonding strength was tested using an electronic tensile testing machine (Dongguan Dazhong Instrument Co., Ltd., Model DZ-101).
[0127] 4) Wet peel strength between the ear glue and the diaphragm
[0128] The negative electrode sheet and the separator prepared by the scheme of the present invention were cut into strips of 20*100 mm, respectively, pressed for 60 s at 100°C and 8 MPa, immersed in an electrolyte at 60°C for 3 days, taken out and dried, and then the bonding strength was tested using an electronic tensile testing machine (Dongguan Dazhong Instrument Co., Ltd., Model DZ-101).
[0129] 5) Internal resistance of battery cell
[0130] Test with an internal resistance tester.
[0131] 6) Capacity retention rate at high temperature 60℃ / 30 days storage
[0132] The soft-pack batteries prepared in the above embodiments and comparative examples were discharged at a constant current of 0.5C to a voltage of 2.7V, then charged at a constant current of 1C to a voltage of 4.3V, and then charged at a constant voltage to a cut-off current of 0.05C. After charging, they were discharged at a constant current of 1C to 2.75V, and the discharge capacity before storage was recorded as C0; they were then charged at a constant current of 1C to a voltage of 4.3V, and then charged at a constant voltage to a cut-off current of 0.05C, at which time the battery was fully charged; the above-mentioned fully charged battery was discharged after being stored at 60°C for 30 days, and the discharge capacity after storage was recorded as C1, then the high temperature storage capacity retention rate (%) = C1 / C0×100%.
[0133] 7) High rate cycle (2C / 1C) room temperature / 500 cycles capacity retention
[0134] For the batteries prepared in the above embodiments and comparative examples, at a temperature of 25°C±2°C, the batteries were discharged at a constant current of 0.5C to a voltage of 2.75V, then charged at a constant current of 1C to a voltage of 4.3V, then charged at a constant voltage to a cut-off current of 0.05C to obtain a fully charged battery, and then discharged at 1C to 2.75V, and the discharge capacity C2 of the battery was recorded; then, the batteries were charged at a constant current of 2C to a voltage of 4.3V, and then charged at a constant voltage to a cut-off current of 0.05C to obtain a fully charged battery, and then discharged at a constant current of 2C to 2.75V, and cycled in this way at 2C for 500 cycles, and the discharge capacity of the battery after the cycle was recorded as C3, then the high rate cycle capacity retention rate (%)=C3 / C2×100%.
[0135] The test results are shown in Table 3.
[0136] Table 3
[0137]
[0138] From Table 3, we can see that:
[0139] The ear glue provided by the present invention can effectively avoid the occurrence of material cross-talk, and is very beneficial to reducing the internal resistance of the battery cell and improving the high-temperature capacity retention rate and high-rate cycle capacity retention rate of the battery.
[0140] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A tip glue, characterized in that: The ear glue is an emulsion, and the surface tension of the emulsion is 45-60 mN / m and the viscosity is above 2000 mPa·s.
2. The ear glue according to claim 1, characterized in that: The solid content of the ear glue is 20-25%.
3. The ear glue according to claim 1, characterized in that: The ear glue comprises a polymer, wherein the polymer comprises a first polymer segment and a second polymer segment, wherein the glass transition temperature Tg of the first polymer segment is ≥50°C, and the glass transition temperature Tg of the second polymer segment is ≤-30°C.
4. The ear glue according to claim 3, characterized in that: The first polymer segment includes a first main structural unit, which is an acrylic structural unit; the second polymer segment includes a second main structural unit, which is an acrylic structural unit; The first polymer segment further comprises a strong polar structural unit, wherein the strong polar structural unit comprises at least one of a structural unit containing a carboxyl group, a hydroxyl group, a cyano group, and an amide group; The second polymer segment further comprises a weak polar structural unit, and the weak polar structural unit comprises at least one of a structural unit containing an aromatic group and an ester group.
5. The ear glue according to claim 3, characterized in that: In the polymer, the mass ratio of the first polymer segment to the second polymer segment is (5-30):(70-95).
6. The ear glue according to any one of claims 3 to 5, characterized in that: The first polymer segment includes a first reactive structural unit, and the second polymer segment includes a second reactive structural unit. The first reactive structural unit and the second reactive structural unit can undergo a polymerization reaction under heating conditions.
7. The ear glue according to claim 6, characterized in that: The first reactive structural unit and the second reactive structural unit are each independently selected from one or more of a hydroxyl group, an isocyanate group, an epoxy group, and a carboxyl group.
8. The ear glue according to claim 6, characterized in that: The mass content of the first reactive structural unit in the first polymer segment is 3-10%; And / or, the mass content of the second reactive structural unit in the second polymer segment is 3-10%.
9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on at least a portion of the surface of the negative electrode current collector; an insulating layer is also disposed on the surface of the negative electrode current collector, and the insulating layer is prepared from an insulating layer slurry comprising the ear glue according to any one of claims 1-8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Polyacrylate water-based adhesive for electrode materials of lithium ion battery, preparation method of adhesive and electrode plates of lithium ion battery
CN104356979A
Polymer binder and preparation and application thereof
CN112909252A
Tab adhesive film for lithium battery tab and preparation method thereof
CN113422163A
Water-based binder for water-based lithium ion battery and preparation method of water-based binder
CN116751335A
Binder for a secondary battery electrode and use thereof
US20220059845A1
Cited By
Diaphragm binder composition, diaphragm and lithium ion secondary battery
CN120775524A
A separator adhesive composition, a separator, and a lithium ion secondary battery
CN120775524B
Tab glue, negative electrode sheet and lithium-ion battery
WO2025256662A1